2015
DOI: 10.1038/icb.2014.103
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 signaling contributes to the high effector activities of interleukin‐15‐derived dendritic cells

Abstract: Dendritic cells (DCs) are important innate and adaptive immune effectors, and have a key role in antigen presentation and T-cell activation. Different lineages of DCs can be developed from hematopoietic progenitors following cytokine signaling, and the various lineages of DCs display distinct morphology, phenotype and functions. There has been limited information on differential cytokine-mediated molecular signaling in DCs. Analyses of surface molecules by flow cytometry and quantitative RNA profiling revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
1
11
0
1
Order By: Relevance
“…TRAF6 is also necessary for activating MAP kinase/AP-1 (28). Further, the Stat3 activity is crucial for IL-15-derived DCs to acquire their antigen-presenting capability and to mediate CD8 + T cell response (29). Consistent with these reports, we demonstrate that ihv-DCs exhibit the constitutive activities of NF-κB, AP-1, and Stat3 as induced by Tax, thereby contributing to their maturation and activation.…”
Section: Discussionsupporting
confidence: 88%
“…TRAF6 is also necessary for activating MAP kinase/AP-1 (28). Further, the Stat3 activity is crucial for IL-15-derived DCs to acquire their antigen-presenting capability and to mediate CD8 + T cell response (29). Consistent with these reports, we demonstrate that ihv-DCs exhibit the constitutive activities of NF-κB, AP-1, and Stat3 as induced by Tax, thereby contributing to their maturation and activation.…”
Section: Discussionsupporting
confidence: 88%
“…Here, our data show that in the absence of SOCS1, STAT3, but not STAT1, is highly activated via phosphorylation. Further, treatment of mice with a STAT3 blocking peptide, STATTIC (39,64,65), reduces both mortality and bacterial burden in iKIR-treated septic mice. STAT3 is activated by IL-6 (66).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many researchers have focused on the exploit of IFN-DC developed by culturing monocytes with GM-CSF and IFN-α as this DCs subset could be more effective than IL-4-DC in the aspect of antigen cross-presentation ( 26 ). Moreover, some studies revealed that the antigen presentation of IL-4-DC relied on the signal transducer and activator of transcription 6 (STAT6) while IFN-DC was not, suggesting that these two DCs have different presenting ways ( 25 , 27 , 28 ). Although IFN-DC and IL-4-DC have been studied for several years, the details of the morphology, phenotype and function of these DCs still need to be explored.…”
Section: Discussionmentioning
confidence: 99%